HUBUNGAN POLA PEMBERIAN ASI DAN MP-ASI DENGAN SKOR PB/U PADA ANAK USIA 6-23 BULAN DI DESA KEMBANGAN KECAMATAN BONANG KABUPATEN DEMAK - Elisa Mawarti; Suyatno Suyatno; Siti Fatimah Pradigdo (Jurnal Kesehatan Masyarakat (Undip), 2022)
Stunting is a chronic nutritional problem that can describe growth failure since before and after birth. Factors that also influence the incidence of stunting include the pattern of breastfeeding and complementary feeding. The stunting rate in Kembangan village, Demak Regency is 80 cases. The purpose of this study was to analyze the relationship between breastfeeding and complementary feeding patterns with Z PB/U scores in children aged 6-23 months. The type of research used is explanatory research with a cross sectional approach. The research population is 138 toodler under two. Research subjects were found to be 65, selected by purposive sampling. The research instrument consisted of a structured questionnaire used to obtain the characteristics of the subject and exclusive breastfeeding, a1x24 hour recall form, and food photo book used to determine the amount of complementary feeding, infantometer for body length, and WHO anthro determines the PB/U index. Statistic test used Spearman Rank correlation. 73,8% of children did not initiate early breastfeeding, 38,5% less breastfeeding, 47,7% less duration of breastfeeding, 69,2% of children not exclusively breastfeed. The first age of children eating inappropriately was 69,2%, the frequency of eating was not appropriate as much as 41,5%, the portion of food was not appropriate as much as 43,1%, the texture of thee food was not appropriate as much as 16,9%. The Z PB/U score for short children was 26,2%. There is a relationship between breastfeeding patterns (p=0,003) and complementary feeding patterns (p=0,001) with Z PB/U scores.  Inappropriate breastfeeding and complementary feeding are related to the Z PB/U score of children aged 6-23 months.